The Fisher hypothesis and nominal interest rate decomposition: A structural VAR approach - Luca Agnello (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
Using Treasury Bill nominal interest rates data for the sample period 1957Q1-2005Q1, we apply the structural VAR methodology developed by Blanchard and Quah (1989) to achieve twofold objective. First of all, we are interested to estimate the time-path of the unobservable variables that, according to the Fisherian theory of interest, determine fluctuations of the nominal interest rates, i.e. the expected inflation and the ex-ante real interest rate components. Secondly, we try to solve the puzzling evidence regarding the apparently nonstationarity of the real interest rates. After accounting for potential infrequent mean shifts in the ex-post real interest rate series, we impose valid long-run neutrality restriction to obtain Structural (identified) VAR and test the magnitude of the Fisher effect over the entire sample of analysis.
Keywords: 330